Conduction disorders as the first hallmark of isolated cardiac sarcoidosis in a highly active individual: a case report. Issue 11 (12th October 2021) - Muccioli, Silvia; Albani, Stefano; Mabritto, Barbara; Musumeci, Giuseppe
Abstract: Background: Cardiac sarcoidosis (CS) is an inflammatory disease with various clinical presentations depending on the extension of cardiac involvement. The disease is often clinically silent, therefore diagnosis is challenging. Case summary: We discuss the case of a middle-aged highly active individual presenting with an occasional finding of low heart rate during self-monitoring. The electrocardiogram shows a Mobitz 2 heart block; thanks to multimodality imaging CS was diagnosed and corticosteroid therapy improved cardiac conduction. Discussion: To our knowledge, this is one of the first documented cases of occasional, early findings of CS in a middle-aged highly active individual who presented with cardiac conduction involvement. Despite the very early diagnosis, multimodality imaging suggested an advanced disease with no oedema detection at the cardiac magnetic resonance. Nevertheless, prompt corticosteroid therapy was able to improve clinical conduction. Although non-sustained ventricular arrhythmias were detected, electrophysiological study allowed to discharge the patient safely without implantable cardioverter-defibrillator implantation. Light-to-moderate physical activity was allowed at mid-term follow-up. A multidisciplinary evaluation should be considered to resume a high-intensity training.